2005
DOI: 10.1177/1534484305278891
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Review of the Management Development Literature

Abstract: SHARON TURNBULL The Leadership Trust FoundationAn appraisal of recent reviews of the literature on management development demonstrates the existence of a number of perspectives on the topic, and this lack of a uniform approach has contributed to confusion about the subject. This article examines a series of recent and existing literature reviews on the topic of management development. It reviews existing and current syntheses of the management development literature and typological models of management develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 21 publications
0
37
0
Order By: Relevance
“…Table1: Descriptive statistics of research variables MD activities are interpreted differently at different organizational levels (Cullen, Turnbull, 2005). Therefore, by using ANOVA post hoc tests, we studied if the means of variables in different management groups varied from each other.…”
Section: Research Methodology and Findingsmentioning
confidence: 99%
See 3 more Smart Citations
“…Table1: Descriptive statistics of research variables MD activities are interpreted differently at different organizational levels (Cullen, Turnbull, 2005). Therefore, by using ANOVA post hoc tests, we studied if the means of variables in different management groups varied from each other.…”
Section: Research Methodology and Findingsmentioning
confidence: 99%
“…The HRM context of an organization is supposed to be a determinant factor of the MD processes adopted by the organization [18]. MD has been viewed as the system of personnel practices to ensure adequate availability of competent and motivated managers [2]. Considering human resource management strategies as a component of MD activities, findings of another study revealed that 9 out of 13 organizations stated that they recruited some formal processes for identification of high-potential managers as candidates to be funded for pursuing some sort of MD activities [4].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The importance of understanding intrinsic barriers to MD engagement stems from the view that MD in the SME context is driven not only by organizational and external environmental forces, but also by the individual needs, disposition and unique characteristics of the owner-manager (Cullen and Turnbull, 2005;Mabey, 2008). Bishop (2008) suggests that an individual's participation in MD activities is not a simple and objective matter of weighing up economic costs against the economic returns of an MD programme.…”
Section: Barriers To Sme Engagement In Management Developmentmentioning
confidence: 99%